Maqashid in Rasail Nur by Badiuzzaman Said Nursi - Robiatul Adawiyah; Abd. Kholid (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study examines the concept of maqâshid contained in Rasail Nur by Badiuzzaman Said Nursi through a literature approach. The Qur'an, as a guideline for the life of Muslims, covers various aspects of life. The maqâshid approach in interpretation aims to achieve human welfare. Maqâshid means the goal or principle desired by the shari'a in establishing laws for the good of humanity. The history of maqâshid began with Imam al-Tirmidzi in the 3rd century AH and continued to develop until the modern era with scholars such as Muhammad Abduh and Sa'id Nursi who expanded the study of maqâshid to various aspects of life. This article explains how Said Nursi applied the concept of maqâshid to understand and apply the teachings of the Qur'an according to the demands of the times.